2016
DOI: 10.1177/1076029615581365
|View full text |Cite
|
Sign up to set email alerts
|

The Trends in Utilizing Nonvitamin K Antagonist Oral Anticoagulants in Patients With Nonvalvular Atrial Fibrillation

Abstract: Dabigatran and rivaroxaban are novel nonvitamin K antagonist oral anticoagulants (NOACs) approved for thromboprophylaxis in atrial fibrillation (AF). In Turkey, like other countries, the efficacy of translation of the clinical trial results and current guideline recommendations into daily clinical practice is yet to be discovered. Using data from medical records of three tertiary care cardiology centers, we identified patients with nonvalvular AF on dabigatran or rivaroxaban treatment. Baseline characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These findings corroborate that receiving ILD doses, especially unintended, might be a risk factor for recurrent ischaemic stroke (Figure D ). Similarly, Kilickiran Avci et al also reported an inappropriate reduced dose in 1/3 of the studied patients with NVAF, with a high risk of stroke, what was considered a worrying pattern of practice.…”
Section: Resultsmentioning
confidence: 90%
“…These findings corroborate that receiving ILD doses, especially unintended, might be a risk factor for recurrent ischaemic stroke (Figure D ). Similarly, Kilickiran Avci et al also reported an inappropriate reduced dose in 1/3 of the studied patients with NVAF, with a high risk of stroke, what was considered a worrying pattern of practice.…”
Section: Resultsmentioning
confidence: 90%
“…Similarly, the lower level of use of the 150-mg strength in the European study may be reflective of the use of lower doses in countries where the 110-mg strength is available. In Turkey, only 45 % of dabigatran use was for the higher strength [ 29 ], and a European survey reported 61 % of dabigatran use in adults was at the 150-mg strength [ 30 ].…”
Section: The Dabigatran Examplementioning
confidence: 99%
“…11 This has led warfarin to remain as the most widely prescribed oral anticoagulant in many countries despite challenges with its management. [12][13][14][15][16][17] Variety of models are used in warfarin management including patient selfmanagement, specialized anticoagulation clinics, and pharmacist-managed anticoagulation clinics. 18 Pharmacistmanaged anticoagulation clinic represents a model that provides patients with more consistent management, closer monitoring, more education, and awareness especially in regard to interacting drugs and food which can ultimately alter warfarin efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%